2018
DOI: 10.5812/ijp.11735
|View full text |Cite
|
Sign up to set email alerts
|

Is Prophylactic Parenteral Paracetamol Effective to Diminish Incidence of PDA in Preterm Neonates? A Randomized Trial

Abstract: Background: Patent ductus arteriosus (PDA) is a common cause of morbidity and mortality among preterm infants. This study aimed to assess the efficacy of prophylactic parenteral paracetamol dosage to decrease rate of ductus patency in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Aikio et al [15] and Bagheri et al [20] administered paracetamol to a group of newborns with PDA. They reported that the outcomes of echocardiography on day 4 showed PDA closure was higher in the treated compared to untreated groups.…”
Section: Resultsmentioning
confidence: 99%
“…Aikio et al [15] and Bagheri et al [20] administered paracetamol to a group of newborns with PDA. They reported that the outcomes of echocardiography on day 4 showed PDA closure was higher in the treated compared to untreated groups.…”
Section: Resultsmentioning
confidence: 99%
“…Sample size turned out to be 26 (13 in each group) considering Two-sided confidence level (1-alpha) 95%, Power (% chance of detecting) 80%, ratio of Controls to Cases as 1, proportion of controls with exposure 71.3% and proportion of cases with exposure 15%. 8 A total of 70 neonates (35 cases and 35 controls) having gestational age less than or equal to 34 weeks were enrolled. Neonates having pulmonary artery atresia, aortic coarctation, genetic disease, persistent pulmonary hypertension, Apgar score at 5 minutes less than 5 or those with blood cord pH below 7.0 were not enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 A recent study from Iran reported frequency of PDA among neonates who were given prophylactic parenteral paracetamol to be 15% in comparison to 71.3% in controls. 8 Some previous trials have exhibited https://doi.org/10.29309/TPMJ/2022.29.01.6528 2 intraventricular hemorrhage (grade 4 and 5) are reduced with the use of prophylactic indomethacin if started within 12 hours of birth and no correlation with neurodevelopmental outcomes was observed. 9 As not much work is conducted in Pakistan looking at possible prophylactic role of parenteral paracetamol on PDA closure, we planned this study to find out the effectiveness of prophylactic parenteral paracetamol to minimize rates of ductus patency among preterm infants.…”
Section: Introductionmentioning
confidence: 99%